2018
DOI: 10.11622/smedj.2017035
|View full text |Cite
|
Sign up to set email alerts
|

Breast reconstruction rate and profile in a Singapore patient population: a National University Hospital experience

Abstract: Introduction: Breast reconstruction is an integral part of breast cancer management, with the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
2
5
0
Order By: Relevance
“…Our five-year trend shows a gradual increase in the rate of BR as in the case in Canada, USA, China, and Singapore (7)(8)(9). This finding may suggest a rise in the awareness of BR.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Our five-year trend shows a gradual increase in the rate of BR as in the case in Canada, USA, China, and Singapore (7)(8)(9). This finding may suggest a rise in the awareness of BR.…”
Section: Discussionsupporting
confidence: 58%
“…The overall trend is an increase in implantbased BR since most patients are opting for immediate breast reconstruction. We state that there is a progressive increase in immediate breast reconstructions over time compared to a predicted decline delayed BR in our tertiary center similar to other hospital-based studies (7)(8)(9)11). Further research into the determinants of timing of the BR needs to be explored, as our study design limited the ability to capture the influences of the trend at our hospital.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The overall rate of breast reconstruction in the present study was 10.7%. Another survey [16] conducted in Singapore found that the breast reconstruction rate from 2001 to 2010 was 24.3%. Albornoz et al [17] reported immediate breast reconstruction trends in the U.S. using the Nationwide Inpatient Sample database from 1998 to 2008.…”
Section: Discussionmentioning
confidence: 99%
“…This variation could be accounted for by the large number of low-volume surgeons in the data base or that there are barriers to offering IBR even for some high-volume surgeons. The Scottish guidelines suggest a target of 10% [ 18 ] and Singapore 20% [ 19 ] despite the well documented safety and psychological and emotional well-being related benefits [ 14 , 15 ]. A Dutch retrospective analysis found key factors inhibiting the decision making of IBR post mastectomy [ 22 ] included higher age (62.2 vs 51.9) and BMI (27 vs 24.3) and failure of surgeon to offer IBR due to predicted need for post mastectomy radiation (29.3%) or just failure of informing the patient (10%).…”
Section: Discussionmentioning
confidence: 99%